Developing Human Resources Through Hidden Curriculum: The experience of Pondok Modern Darussalam Gontor, Indonesia - M. Akrim Mariyat (At-Ta'dib, 2011)
Pondok Modern Gontor, as a modern type of pesantren, grows very fast inthe term of quality and quantity, the amount of applicants is growing everyyear, and its graduates spread through Indonesian provincies. They take variouskinds of role e.g politicians, traders, civil-servants, rectors, deans, teachers,lecturers, doctors, muballighs, religious leadders, head of pesantrens etc.Due to the variety of occupation they take, and status they gain, it raisedsome questions related to the notion as well as the phylosophy of PondokModern, the curriculum they provide and the process they carried out. One ofthe answers is probably because the Pondok run boarding school system whichmakes Pondok Modern different from other educational institutions in general.By this system many kinds of educational process in the form of pro grammeand activities could be easily undertaken, because the three centres of education(home - school - community ) are mixed in one campus. Students are accustomedto practice “learning by doing” method and are supervised by their elders andteachers.Questions emerge due to the uniqueness of Pondok Modern eg. Whydid Gontor adopt boarding school system? How was the curriculum constructedand applied? And there are still a lot more questions related to this matter. Thispaper tries to offer some answers to these questions.